Historical category of Commercial Law analyzed in light of the evolution of the Revista de Ciencias Jurídicas - Chaves Corrales, Pedro (2023)
Commercial Law in Costa Rica as a historical category is a topic of relevance for understanding the economic and legal development of the country. Over the years, this field of law has undergone major transformations that have been driven by changes in the social, political and economic context at both the national and international levels. Commercial law in Costa Rica has evolved from an initial stage marked by agricultural trade and the influence of Spanish legislation, to become a modern and dynamic discipline, capable of regulating the complex commercial processes of today.